Resting Metabolic Rate of Individuals - Abel Plaza-Florido; Juan M. A. Alcantara (Metabolites, 2023)
The resting metabolic rate (RMR) represents the energy required to sustain normal body functions and homeostasis in an awake individual under ambient thermoneutral conditions and during rest [...]